A Study Of Mixing Performance In A Microreactor Using Computational Fluids Dynamic (Cfd) - Termizi, Siti Nor Azreen Ahmad (2016)
Moving towards better future of chemical engineering in respond to the changing need and demand requires complementary of environmental, safety and cost in production of a product. The growth of process intensification has found to be the path to achieve this goal. Microreactor is one of the intensified equipment which is a product of process intensification, which requires understanding of the fundamental knowledge in order for it to be fully utilised. Therefore, the purpose of this study is to characterize mixing and to evaluate mixing performance of the Standard Slit Interdigital Micro Mixer (SSIMM) mixing element with different configurations of microchannel. Investigation on the effects of microchannel configurations, inlet velocity and diffusion coefficient toward mixing intensity was conducted using Computational Fluid Dynamics (CFD) simulation. The result showed that inlet velocity has significance effects on the mixing performance which represented by mixing intensity in this study. Higher inlet velocity resulted in lower mixing quality. The inlet velocity of 1000 μm/s and 10000 μm/s give low mixing intensity and incomplete mixing at the end of discharge slit position. High diffusion coefficient value gave faster mixing process. The mixing process occurred instantaneously at diffusion coefficient value of 1.0x 10-8 m2/s. The mixing intensity profile of corrugated microchannel which represents the mixing element of the SSIMM showed a smooth trend as compared to the other two microchannel configurations.